MEDIA PEMBELAJARAN BAHASA ISYARAT DENGAN METODE MULTIMEDIA DEVELOPMENT LIFE CYCLE - Bustamin, Syamsumar; Hamdani, Ibnu Mansyur; Hadi, Abri (Universitas Methodist Indonesia, 2023)
Interactive learning media is one manifestation of the use of information and communication technology in the field of education. One part of the use of information technology is Augmented Reality, where the use of Augmented Reality in education is still lacking. Education is not only for those with normal physical abilities, but all people have the right to receive an education that is general, as well as children with special characteristics, such as deaf students who are at SLB Negeri 1 Palopo. Deaf students are students who have lost the ability to hear which hinders the process of language information through hearing, because of these limitations the teaching and learning process will become an obstacle, so other media are needed to visualize the alphabetic sign language code so that it can be learned easily and interactively. Augmented Reality is the right technology to overcome this. The implementation of Augmented Reality is used for Android mobile devices with the Multimedia Development life Cycle.